Involvement of mucosal flora and enterochromaffin cells of the caecum and descending colon in diarrhoea-predominant irritable bowel syndrome - Jingze Yang (BMC, 2021)
Abstract Background Accumulating evidence supports the pivotal role of intestinal flora in irritable bowel syndrome (IBS). Serotonin synthesis by enterochromaffin (EC) cells is influenced by the gut microbiota and has been reported to have an interaction with IBS. The comparison between the microbiota of the caecal and colonic mucosa in IBS has rarely been studied. The aim of this study was to investigate the relationship between the gut microbiota, EC cells in caecum and descending colon, and diarrhoea-predominant IBS (IBS-D) symptoms. Results A total of 22 IBS-D patients and 22 healthy controls (HCs) were enrolled in our study. Hamilton anxiety (HAM-A) and Hamilton depression (HAM-D) grades increased significantly in IBS-D patients. In addition, the frequency of defecation in IBS-D patients was higher than that in HCs. Among the preponderant bacterial genera, the relative abundance of the Ruminococcus_torques_ group increased in IBS-D patients in caecum samples while Raoultella and Fusobacterium were less abundant. In the descending colon, the abundance of the Ruminococcus_torques_group and Dorea increased in IBS-D patients and Fusobacterium decreased. No difference was observed between the descending colon and caecum in regards to the mucosal-associated microbiota. The number of EC cells in the caecum of IBS-D patients was higher than in HCs and the expression of TPH1 was higher in IBS-D patients both in the caecum and in the descending colon both at the mRNA and protein level. Correlation analysis showed that the Ruminococcus_torques_group was positively associated with HAM-A, HAM-D, EC cell number, IBS-SSS, degree of abdominal pain, frequency of abdominal pain and frequency of defecation. The abundance of Dorea was positively associated with EC cell number, IBS-SSS, HAM-A, HAM-D and frequency of abdominal pain. Conclusions EC cell numbers increased in IBS-D patients and the expression of TPH1 was higher than in HCs. The Ruminococcus torques group and Dorea furthermore seem like promising targets for future research into the treatment of IBS-D patients.